Approaching the Maqashid Sharia of Marriage from the perspective of Al-Qur'an Fiqh - Kasim, Dulsukmi; Sumanto, Dedi (KALOSARA: Family Law Review, 2025)
Placing marriage from the perspective of divine norms (Fiqh al-Qur'an) is a logical and spiritual reference that is always relevant for humans. According to the Qur'an, desires are paired with the instincts of all creatures, including humans. The confirmation is in surah Yasin/36: 36 and al-Zariyat/51: 49. The repetition of the word "marriage" in the Qur'an along with three other words that are equivalent in meaning to the word marriage (zauj, istimta', and ma 'aqadat aymanukum) establishes five meanings in the word marriage, namely sexual intercourse, strong bond, pairing, uniting, and gathering. The use of the word marriage in the Qur'an is only directed at humans. Before the hijrah, the marriage verses that came down talked more about the philosophical meaning and purpose of marriage. After the hijrah, the marriage verses talked more about technical matters of marriage, such as details about which women could and could not be married. In addition, three main things are maqashidunnikah according to the Qur'an, namely: 1) A means of channelling lust that is permitted by religion/sharia; 2) A way to maintain human descendants on earth so that their civilisation remains sustainable and is protected from extinction; 3) A medium to achieve peace of life (sakinah) and happiness in the world and the hereafter. This finding is relevant to the theory of maqashid sharia that marriage is part of hifzhuddin, hifzhunnafs and hifzhunnasl, all of which are included in daruriyyat for humans. This paper contribute to reinterprets the meaning of marriage in the Qur'an as an integration of spiritual, social, and maqashid sharia values in human life.Keywords: Maqashid Sharia, Marriage, al-Qur'an Fiqh